First Prize International Olympic Museum, Lausanne Switzerland Competition - Antoniou, Klitsa (My University, 2026)
First Prize International Olympic Museum, Lausanne, Switzerland Competition. Represent Cyprus in an International Competition at the Olympic Museum
Keywords: Arts and entertainment